2017
DOI: 10.1111/lang.12266
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processing of Congruent and Incongruent Audiovisual Speech in School‐Age Children and Adults

Abstract: Seeing articulatory gestures enhances speech perception. Perception of auditory speech can even be changed by incongruent visual gestures, which is known as the McGurk effect (e.g., dubbing a voice saying /mi/ onto a face articulating /ni/, observers often hear /ni/). In children, the McGurk effect is weaker than in adults, but no previous knowledge exists about the neural‐level correlates of the McGurk effect in school‐age children. Using brain event‐related potentials, we investigated change detection respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…The research on communication of people with deafness associated with the Effects of McGurk suggests that visual stimuli affect the processing of auditory stimuli in adulthood and in children although weaker (Heikkilä et al, 2018). Several other studies have shown that children with hearing impairment have language skills (such as vocabulary and syntactic knowledge) that are more predictive in reading ability, compared to their phonological awareness (Geers & Hayes, 2011;Mayberry et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The research on communication of people with deafness associated with the Effects of McGurk suggests that visual stimuli affect the processing of auditory stimuli in adulthood and in children although weaker (Heikkilä et al, 2018). Several other studies have shown that children with hearing impairment have language skills (such as vocabulary and syntactic knowledge) that are more predictive in reading ability, compared to their phonological awareness (Geers & Hayes, 2011;Mayberry et al, 2011).…”
Section: Introductionmentioning
confidence: 99%